2020
DOI: 10.1039/c9ra10825d
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the seed-assisted synthesis of zeolites without organic structure-directing agents: insights from the CHA case

Abstract: Herein, the crystallization behaviour of the CHA zeolite synthesized via the seed-assisted method and in the absence of an organic structure-directing agent has been revisited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…Furthermore, the NMR spectroscopic results confirmed the formation of crystalline CHA zeolite. The 27 Al NMR spectrum contains only one peak at 57.8 ppm corresponding to tetrahedrally coordinated Al (Supporting Information, Figure S1), while the 29 Si NMR spectrum contains peaks at −89.3 ppm, −93.6 ppm, −99.1 ppm, −104.6 ppm, and −109.1 ppm corresponding to Q 0 (4Al), Q 1 (3Al), Q 2 (2Al), Q 3 (1Al), and Q 4 (0Al) silicon tetrahedrally coordinated, respectively [24] . A Si/Al ratio of 2.0 was estimated according to the equation of Engelhardt and Michel using the 29 Si NMR data [25]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the NMR spectroscopic results confirmed the formation of crystalline CHA zeolite. The 27 Al NMR spectrum contains only one peak at 57.8 ppm corresponding to tetrahedrally coordinated Al (Supporting Information, Figure S1), while the 29 Si NMR spectrum contains peaks at −89.3 ppm, −93.6 ppm, −99.1 ppm, −104.6 ppm, and −109.1 ppm corresponding to Q 0 (4Al), Q 1 (3Al), Q 2 (2Al), Q 3 (1Al), and Q 4 (0Al) silicon tetrahedrally coordinated, respectively [24] . A Si/Al ratio of 2.0 was estimated according to the equation of Engelhardt and Michel using the 29 Si NMR data [25]…”
Section: Figurementioning
confidence: 99%
“…The 27 Al NMR spectrum contains only one peak at 57.8 ppm corresponding to tetrahedrally coordinated Al (Supporting Information, Figure S1), while the 29 Si NMR spectrum contains peaks at À89.3 ppm, À93.6 ppm, À99.1 ppm, À104.6 ppm, and À109.1 ppm corresponding to Q 0 (4Al), Q 1 (3Al), Q 2 (2Al), Q 3 (1Al), and Q 4 (0Al) silicon tetrahedrally coordinated, respectively. [24] A Si/Al ratio of 2.0 was estimated according to the equation of Engelhardt and Michel using the 29 Si NMR data. [25] The mechanism of selective CO 2 adsorption by OSDAfree nanosized CHA zeolite was investigated by several complementary in situ methods.…”
mentioning
confidence: 99%
“…Moreover, the intensity of XRD reflections of the final catalysts shows lower crystallinity compared to that of the initial zeolites owing to the amorphous character of the silica binder. Furthermore, the XRD reflections also shifted toward lower 2θ, suggesting the presence of more Si-O bonds [21,22,23], which are likely due to the crystallization of some parts of the silica binder into the zeolite phase. Note that the Si-O has a shorter bond length compared to the Al-O, thus, the dspacing will be constricted, resulting in lower θ or 2θ based on the Bragg equation, nλ = 2d sin θ.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 1 Schematic illustrations of a four selected zeolite frameworks and their micropore systems (Smeets and Zou 2017) and the synergistic role of Na + and K + in directing the formation of CHA frameworks (Kadja et al 2020a) Due to the existence of such unique and comprehensive features in their structure, zeolites have some physicochemical properties as follows:…”
Section: Structure and Physicochemical Propertiesmentioning
confidence: 99%
“…However, OSDA has disadvantages because they are usually expensive compounds, and the most common way to remove the OSDA is through combustion. Some works reported that minimizing the amount of OSDAs used in the synthesis (Ferdov 2017;Kadja et al 2017Kadja et al , 2020aKadja et al , 2021aKadja et al , 2021bRilyanti et al 2016) will less damage the zeolite structure during the removal of the OSDAs. Furthermore, OSDAs are also utilized intensively to synthesize hierarchical and layered or two-dimensional (2D) zeolites.…”
Section: Zeolite Synthesismentioning
confidence: 99%